Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
h(x)=2^(x-3)
replace h(x) with y:
y=2^(x-3)=(2^x)*(2^-3)=(2^x)/(2^3)=(2^x)/8
y=2^x/8
solve for x:
8y=2^x
log2(8y)=x
replace h(x) with y:
y=2^(x-3)=(2^x)*(2^-3)=(2^x)/(2^3)=(2^x)/8
y=2^x/8
solve for x:
8y=2^x
log2(8y)=x
Answer:
[tex]f^{-1}(x)=2^x+3[/tex]
Step-by-step explanation:
Given:
[tex]y=\log_2(x-3)[/tex]
To find the inverse of the given function, make x the subject.
[tex]\textsf{Apply log law}: \quad \log_ab=c \iff a^c=b[/tex]
[tex]\implies 2^y=x-3[/tex]
Add 3 to both sides:
[tex]\implies x=2^y+3[/tex]
Swap x for [tex]f^{-1}(x)[/tex] and y for x:
[tex]\implies f^{-1}(x)=2^x+3[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.